1991
DOI: 10.1177/39.11.1655877
|View full text |Cite
|
Sign up to set email alerts
|

Ultracytochemical characteristics of cultured goat brain microvascular endothelial cells [corrected]

Abstract: This ultrastructural study was undertaken to determine the localization ofcytochemically demonstrable blood-brain bartier (BBB)-associated enzymatic activities and ofsome nonenzymatic constituents in sheep brain microvascular endotheial cells (ECs) growing in vitro. Positive reactions for alkaline phosphatase (AP), 5'-nudeotidase (5'N), transport ATPase (Na ,K-ATPase), and adenosine diphosphatase (AD1 ase) were present on both apical and basolateral plasma membranes (PMs) ofthe ECs. The reaction for calcium-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
0
15
1
Order By: Relevance
“…Conversely, the TNAP activity was mainly detected in the abluminal plasma membrane of rat BCECs (Inomata et al 1984), in luminal plasma membrane of mice brain capillaries and in both luminal and abluminal plasma membranes in arterioles (Vorbrodt et al 1986). Again, the TNAP activity is detected both on the luminal and abluminal walls of BCECs in frog (Lazzari et al 1989) and goat (Vorbrodt and Trowbridge 1991). This discrepancy of localisation comes likely from methods used to fix tissue that inactivate the TNAP.…”
Section: Cell Localisationmentioning
confidence: 80%
See 1 more Smart Citation
“…Conversely, the TNAP activity was mainly detected in the abluminal plasma membrane of rat BCECs (Inomata et al 1984), in luminal plasma membrane of mice brain capillaries and in both luminal and abluminal plasma membranes in arterioles (Vorbrodt et al 1986). Again, the TNAP activity is detected both on the luminal and abluminal walls of BCECs in frog (Lazzari et al 1989) and goat (Vorbrodt and Trowbridge 1991). This discrepancy of localisation comes likely from methods used to fix tissue that inactivate the TNAP.…”
Section: Cell Localisationmentioning
confidence: 80%
“…Indeed, many authors have reported the existence of BBB in many vertebrates (Abbott 2005). Several studies demonstrated the presence of AP activity in capillary endothelium of rat brain (Meunier and Bouchaud 1978;Liu et al 1979;Inomata et al 1984), mouse brain (Vorbrodt et al 1981(Vorbrodt et al , 1986, goat brain (Vorbrodt and Trowbridge 1991), avian species (Stewart and Wiley 1981), frog brain (Latker et al 1987;Lazzari et al 1989), cat brain (Vorbrodt et al 1985), primate brain (Shi and Audus 1994), bovine brain (Brunel et al 1969). Recently, the impermeability of cerebral microvessels has been first reported in zebrafish following in vivo experimentation of permeability assays (sulfo-NHS-biotin and horseradish peroxydase) and immunoreactivity towards integral proteins (Claudin-5 and Zonula Occludens-1) of the tight junctions (Jeong et al 2008).…”
Section: Species Specificitymentioning
confidence: 95%
“…Alkaline phosphatase is an enzyme anchored in the apical membrane of cells that possess P-glycoprotein (Moss, 1982;1992;Robinson & Karnovsky, 1983;Fojo et al, 1987;Vorbrodt & Trowbridge, 1991). All these cells -intestinal epithelium, kidney proximal tubules, hepatocytes, blood-brain barrier, placenta -are lining surfaces endowed with intense transport activities (secretion and absorption).…”
Section: Calculations and Statisticsmentioning
confidence: 99%
“…Magnification 300 ase (g-GT) has been observed upon in vitro cultivation (Meyer et al 1990). In other in vitro model systems of the blood brain barrier, the ALP activity was reported to be not entirely absent, but reduced in comparison to in vivo conditions and decreasing with increasing passage number (Vorbrodt and Trowbridge 1991;Shi and Audus 1994). When, on the other hand, cell differentiation into capillary-like sprouts was induced in immortilized brain endothelial cells by b-FGF, these sprouts resumed expression of ALP (Roux et al 1994).…”
Section: Discussionmentioning
confidence: 95%
“…Another typical alteration observed in endothelial cells in vitro is a loss of plasmalemmal vesicles (Vorbrodt and Trowbridge 1991;Roberts and Sandra 1993). Since ALP activity in myocardial capillary endothelial cells is mainly located in plasmalemmal vesicles, i.e., on the plasmalemmal membrane ), this finding is likely to represent the morphological correlate of the observed enzyme activity loss.…”
Section: Discussionmentioning
confidence: 98%